Research on the Influence of Horizontal Thermal Advection on Surface Energy Balance in Zoige Alpine Wetland - Xuancheng LU; Jun WEN; Yue YANG; Hui TIAN; Wenhui LIU; Yueyue WU; Yuqin JIANG (Gaoyuan qixiang)
The near-surface energy budget closure has always been a scientific hot topic in the land-surface processes research， especially over the underlying surface of heterogeneous wetlands.In this investigation， the horizontal thermal advection caused by thermal inhomogeneity of the underlying surface over the wetland is calculated based on the data of the Flower-lake observation field in the Zoige alpine wetland.With considering the horizontal thermal advection， its contribution to the near-surface energy closure is analyzed.The results show that the mean horizontal thermal advection of the Zoige wetland is 22.9 W·m-2， and the maximum value can reach 58.7 W·m-2 in the daytime of summer 2017.After introducing the horizontal thermal advection and soil heat storage into the near-surface energy balance equation， the near-surface energy closure ratio increased from 41.8% to 67.9% in summer.The contribution of horizontal thermal advection was 5.8%， that of soil thermal storage was 20.1%， and that of plant photosynthetic thermal storage was 1.0%.The diurnal variation of the near-surface horizontal thermal advective is equivalent to the sensible heat flux in Zoige wetland， and the maximum diurnal variation is about one third of the thermal storage of the wetland soil.